2009
DOI: 10.1002/jqs.1280
|View full text |Cite
|
Sign up to set email alerts
|

Surface exposure dating of Late Pleistocene glaciations at the Dedegöl Mountains (Lake Beyşehir, SW Turkey)

Abstract: Situated on the interior side of the western central Taurus Mountains of SW Anatolia, the Muslu Valley in the Dedegö l Mountains (Mt Dipoyraz: 378 37 0 07 00 N, 318 19 0 42 00 E, 2992 m above sea level (a.s.l.)) represents the lower part of a formerly glaciated valley system of $7.5 km in length. Surface exposure ages with cosmogenic 10 Be and 26 Al date a glacier expansion out of the Muslu Valley 24.3 AE 1.8 ka ago (1s confidence interval) and give evidence for pronounced glacier advances prior to the global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 47 publications
(65 reference statements)
3
42
0
Order By: Relevance
“…Later about 15.1 ± 0.9 ka in the Late Glacial period, the glaciers retreated slightly and remained stable for a short time. Similar OSL ages (17.7 ± 4.4 ka) have been obtained by Bayrakdar (2012) (Zahno et al, 2009). The Muslu Valley on the eastern side of the mountains has two lateral moraines extending to an elevation of 1400 m which were dated by Zahno et al (2009).…”
Section: Western Taurussupporting
confidence: 87%
See 2 more Smart Citations
“…Later about 15.1 ± 0.9 ka in the Late Glacial period, the glaciers retreated slightly and remained stable for a short time. Similar OSL ages (17.7 ± 4.4 ka) have been obtained by Bayrakdar (2012) (Zahno et al, 2009). The Muslu Valley on the eastern side of the mountains has two lateral moraines extending to an elevation of 1400 m which were dated by Zahno et al (2009).…”
Section: Western Taurussupporting
confidence: 87%
“…Moraines are exposed to cosmic rays from the moment the glacier starts to retreat and it is assumed that the deposited material has not been exposed to cosmic rays previously, thus the minimum age of deposition of the moraine is calculated as the beginning of glacial retreat (Zreda and Phillips, 2000). In Turkey by measurement of 36 Cl and 10 Be cosmogenic isotopes on moraines, the chronology of Quaternary glaciation has been revealed in detail and paleoclimate interpretations have been made (Akçar et al, 2007;Sar›kaya et al, 2008;2009;Sar›kaya, 2009;Zahno et al, 2009;2010;Zreda et al, 2011;Akçar et al, 2015;.…”
Section: Method: Cosmogenic Surface Exposure Datingmentioning
confidence: 99%
See 1 more Smart Citation
“…The last decade has seen a large number of studies published in this region (Akçar et al 2007(Akçar et al , 2008(Akçar et al , 2014Sarıkaya et al 2008Sarıkaya et al , 2009Sarıkaya et al , 2014Zahno et al 2009Zahno et al , 2010Zreda et al 2011;Reber et al 2014;Ç iner et al 2015). These are either 10 Be or 36 Cl exposure age studies.…”
Section: Turkey and The Near Eastmentioning
confidence: 99%
“…Makos et al, 2013), and in Mediterranean mountains (Akçar et al, 2007(Akçar et al, , 2014Zahno et al, 2009;Giraudi, 2012). Ivy-Ochs et al (2004a) reported that the Rhône piedmont glacier collapsed at 21-19.1 ka.…”
Section: Introductionmentioning
confidence: 98%